Intuition, empathy, and intellectual humility in psychotherapy. A philosophical perspective - Stefanello, Eugenia (Frontiers in Psychology, 2025)
Intuition is often considered a crucial tool in psychotherapy, especially in guiding the therapist's clinical strategy. However, the specifically epistemic question of how to guarantee its accuracy deserves to be better explored. Drawing on Bohart's account of intuition in psychotherapy, I will first distinguish intuition from the closely related but distinct phenomenon of empathy, and then argue that the epistemic role of intuition in psychotherapy seems to be that of a salience detector. Second, I will demonstrate why intuition must be accurate to be therapeutically effective, thereby avoiding potential related epistemic and ethical pitfalls. Finally, I will conclude by suggesting that Bohart's proposed reflective feedback loop process appears insufficient to achieve this result, and that the epistemic virtue of intellectual humility seems a prerequisite for initiating and successfully carrying out this process.